Pengaruh Customer Review dan Celebrity Endorsement terhadap Purchase Intention dengan Trust sebagai Variabel Moderasi pada Skincare Produk Serum Somethinc - Ainun, Hasnah; Tantra, Tarandhika (Jurnal Ilmu Manajemen, 2023)
The demand for skincare products in Indonesia is increasing as consumers become more aware of the importance of skincare. Serum is a popular skincare product in Indonesia, particularly among women who prioritize skin care. However, Somethinc has yet to become the top choice for consumers, with only 2.6% of customers indicating that they use Somethinc serum. To increase purchase intention, Somethinc can utilize eWOM communication such as customer reviews or celebrity endorsements. This study aims to investigate the influence of customer reviews and celebrity endorsements on purchase intention for Somethinc serum products and to determine whether trust moderates the effect of customer reviews and celebrity endorsements on purchase intention. This study employs a quantitative research method with non-probability sampling of 388 respondents and uses Structural Equation Modeling-Partial Least Square (SEM-PLS) for data analysis. The results demonstrate that customer reviews and celebrity endorsements significantly and positively influence purchase intention for Somethinc serum products. However, trust does not moderate the effects of customer reviews and celebrity endorsements on purchase intention for Somethinc products. The suggestion for Somethinc to consider is increasing the use of celebrity endorsers through marketing campaigns that collaborate with celebrities who have a positive image and are appropriate for their target market.